Assessment of healthcare organizational readiness for change: A fuzzy logic approach - V. Vaishnavi; M. Suresh (Journal of King Saud University: Engineering Sciences, 2022)
The primary purpose of the paper is to identify the level of organisation's readiness for change in order to improve change in health organizations. The current research is focused to establish an evaluation model for organizational readiness. Fuzzy methods offer a streamlined and analytical environment, which enables to design, analyse or test models in a reasonable shorter time compared to other approaches. Development of conceptual framework through defining enablers, criteria and attributes based on literature review and expert opinion. Four enablers are defined for the development of a conceptual model along with 12 criteria and 38 attributes. Fuzzy logic approach is performed by two levels of analysis. In order to determine the organizational readiness level of the hospital, the Fuzzy Organizational Readiness Index (FORI) and Fuzzy Performance Importance Index (FPII) were calculated. The FORI can be estimated as the “Averaged Ready” (3.48, 5.21, 6.95) and FPII is calculated to identify eighteen weaker attributes that necessities management attention to prepare a hospital for the process of change. The suggested structure strengthens the ability of administrators to effectively incorporate improvements in their organizations.